Modification of a Density-Based Spatial Clustering Algorithm for Applications with Noise for Data Reduction in Intrusion Detection Systems - Wiharto, Wiharto; Wicaksana, Aditya K.; Cahyani, Denis E. (INTERNATIONAL JOURNAL of FUZZY LOGIC and INTELLIGENT SYSTEMS, 2021)
Monitoring activity in computer networks is required to detect anomalous activities. This monitoring model is known as an intrusion detection system (IDS). Most IDS model developments are based on machine learning. The development of this model requires activity data in the network, either normal or anomalous, in sufficient amounts. The amount of available data also has an impact on the slow learning process in the IDS system, with the resulting performance sometimes not being proportional to the amount of data. This study proposes an IDS model that combines DBSCAN modification with the CART algorithm. DBSCAN modification is performed to reduce data by adding a MinNeighborhood parameter, which is used to determine the distance of the density to the cluster center point, which will then be marked for deletion. The test results, using the Kaggle and KDDCup99 datasets, show that the proposed system model is able to maintain a classification accuracy above 90% for 80% data reduction. This performance was also followed by a decrease in computation time, for the Kaggle dataset from 91.8 ms to 31.1 ms, while for the KDDCup99 dataset from 5.535 seconds to 1.120 seconds KCI Citation Count: 0